Konstruksi Teologi Persahabatan Kontekstual: Membaca Ulang Narasi Persahabatan Yonatan dan Daud dari Lensa Seorang Batak Toba - Roy Charly Sipahutar (Indonesian Journal of Theology, 2023)
Indonesian theologians over the past decade have shown increasing interest in discussing various aspects of friendship. Unfortunately, not many have explored it from the perspective of the Old Testament (OT), in spite of the fact that several OT narratives explicitly depict interpersonal friendship—one of which tells of the close relationship between Jonathan and David as found passim throughout 1 and 2 Samuel. This article seeks both a deeper understanding of as well as fresh insights from the Jonathan-David narrative, which will be re-read through the lens of Batak Toba friendship as represented by marpadan and maraleale. Sociological, anthropological, and spiritual values of friendship are intertwined in these two important terms. In re-reading the Jonathan-David narrative, marpadan (intricate solidarity) and maraleale (deep friendship) are placed in a constructive dialogue with bĕrîth (covenant or testament in biblical Hebrew). The results of this re-reading through a Batak Toba perspective shows that the Jonathan-David relationship was not limited only to their interpersonal relationship but later expands to include intercommunal relations. Friendship is thus the willingness of both parties to open up, blend together, and always be progressively subject to mutual self-evaluation.